Tau-driven 26S proteasome impairment and cognitive dysfunction can be prevented early in disease by activating cAMP-PKA signaling - Myeku, Natura (Nat Med, 2015)
The ubiquitin proteasome system (UPS) degrades misfolded proteins including those implicated in neurodegenerative diseases. We investigated the effects of tau accumulation on proteasome function in a mouse model of tauopathy and in a cross to a UPS reporter mouse (line Ub-G76V-GFP). Accumulation of insoluble tau was associated with a decrease in the peptidase activity of brain 26S proteasomes, higher levels of ubiquitinated proteins and undegraded Ub-G76V-GFP. 26S proteasomes from mice with tauopathy were physically associated with tau and were less active in hydrolyzing ubiquitinated proteins, small peptides and ATP. 26S proteasomes from normal mice incubated with recombinant oligomers or fibrils also showed lower hydrolyzing capacity in the same assays, implicating tau as a proteotoxin. Administration of an agent that activates cAMP–protein kinase A (PKA) signaling led to attenuation of proteasome dysfunction, probably through proteasome subunit phosphorylation. In vivo, this led to lower levels of aggregated tau and improvements in cognitive performance.